ASSESSMENT OF KNOWLEDGE AMONG NURSES ABOUT WOUND INFECTION IN CARDIOTHORACIC SURGERY PATIENTS - NAWAZ , R; BIBI , S (Biological and Clinical Sciences Research Journal, 2023)
Cardiothoracic nurses are crucial in providing wound care to patients following cardiac surgery. However, there is limited research on their knowledge and competency in wound management, despite the high incidence of wound infections observed in previous studies. Therefore, this study aimed to assess the knowledge and competency of staff nurses regarding wound management while also investigating potential differences in knowledge between nurses working in private and public hospitals. The study utilized a descriptive design and employed a self-reported questionnaire to evaluate the knowledge of staff nurses in cardiac wound management. A sample of 156 nurses from private and public hospitals was selected, and the questionnaire was distributed among them. Total knowledge scores were calculated, and the data were analyzed using descriptive and inferential statistical methods. The response rate for the study was 55.05%, with a total of 87 nurses participating. The findings of the study revealed several knowledge deficits among cardiothoracic nurses. These deficits were primarily related to wound healing, recognizing the signs and symptoms of surgical site infections, and understanding the specific aspects of cardiac wounds. Many nurses demonstrated uncertainty regarding the appropriate cleaning agents for washing cardiac wounds and lacked awareness of when the initial post-operative dressing should be changed. Based on these results, it is evident that measures need to be taken to improve the knowledge and competency of nurses in wound management. Seminars and workshops should be organized to keep nurses updated with the latest advancements and guidelines in wound care. Additionally, further training opportunities should be provided to enhance their understanding and proficiency in managing wounds specific to cardiothoracic surgeries. In conclusion, the study highlights the importance of addressing the knowledge gaps among cardiothoracic nurses regarding wound management. By equipping nurses with comprehensive knowledge and skills in this area, we can improve patient outcomes, reduce the incidence of surgical site infections, and alleviate the burden on healthcare systems.